Design and additive manufacturing of biodegradable patient-specific implants for bone regeneration (Transactions on Additive Manufacturing Meets Medicine, 2023)
Critical-sized bone defects due to trauma, infection, or tumour resection are defined as the smallest defect that will not heal over one’s lifetime without (surgical) treatment [1]. Despite multiple innovations in the 21st century, current treatment options have significant limitations and there is a strong demand for clinically translatable treatment alternatives, such as scaffold-guided bone regeneration (SGBR) [2]. Our interdisciplinary team has studied tissue engineering applications with biodegradable 3D-printed scaffolds for critical-sized bone defects over the last 17 years in pre-clinical trials and demonstrated successful bone regeneration [3–5]. These findings were recently translated into a clinical setting, and we were able to provide bespoke SGBR solutions for selected patients in Australia and Germany who suffered critical-sized bone defects of 10 to 34 cm [6,7]. The scaffolds were designed in close collaboration with the treating surgeon and prototyped in-house using fused filament fabrication with polylactic acid (PLA) and finally 3D-printed using medical-grade polycaprolactone tricalcium phosphate, sterilized, and shipped to the hospital by a certified supplier.  Here, we are presenting the design process from the computed tomography images to the final prototype along with its challenges and resulting opportunities for a series of clinical cases where a patient-specific 3D-printed scaffold was required.Author’s statement Conflict of interest: D. W. Hutmacher is a cofounder and shareholder of Osteopore International Pty Ltd. The other authors state no conflict of interest. Informed consent: Informed consent has been obtained from all individuals included in this study. Acknowledgments: The authors would like to thank Drs M. Wagels, B. M. Holzapfel, and F. Hildebrand for their clinical feedback and opportunities. Research funding: This work was supported by the Australian Research Council (ARC) Industrial Transformation Training Centre for Multiscale 3D Imaging, Modelling, and Manufacturing (M3D Innovation) [IC 180100008], and the Jamieson Trauma Institute (PhD scholarship for B. Herath), a collaboration of Metro North Hospital and Health Service and the Motor Accident Insurance Commission.References[1] Schemitsch EH, J Orthop Trauma. 2017, 31 Suppl 5:S20-S22.[2] Laubach M, et al., J Funct. Biomater. 2023, 14(7), 341[3] Sparks DS, et al., Nat Protoc. 2020, 15(3):877-924.[4] Sparks DS, et al., Sci Adv. 2023, 9(18)[5] Berner A, et al., Acta Biomater. 2013, 9(8):7874-84.[6] Castrisos G, et al., J Plast Reconstr Aesthet Surg. 2022,75(7):2108-2118[7] Laubach M, et al., J Orthop Translat. 2022, 16;34:73-84
Keywords: patient specific implant; Bone scaffold; Clinical Workflow; 3D-printing; bone regeneration